The Role of Fluoride-Containing Toothpastes in Hygienic Oral Care in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article presents data on oral hygiene items and products for children, as well as rules and features of their use. Pediatric dentists recommend hygienic oral care for children before teething. The first hygiene items may be finger pads and sanitary napkins. Teeth brushing should begin after the first teeth appear. Indications for the use of toothpastes in children and training for adults in their use are described in order to obtain the benefits of using fluoride-containing toothpaste.